PENGARUH KUALITAS PRODUK DAN HARGA PAKAIAN SECOND IMPORT TERHADAP KEPUASAN KONSUMEN (Studi Pada Toko Brandsek di Desa Gas Alam Muara Badak) - Noor, Muhammad; Johansyah; Zainuddin, Muhammad (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2022)
The influence of product quality and the price of second-import clothing on consumer satisfaction at a brandsek store in the natural gas village of Muara Badak. Clothing is a primary human need that has benefits other than food, drink, shelter and so on where clothing can provide comfort, appropriateness, and security to cover the body in everyday life. However, with the development of the times, clothing can be used as a symbol of status, position, or position for the wearer. Everyone has a lifestyle that is characteristic of each, this lifestyle is a factor in choosing a product, the product chosen must be in accordance with consumer tastes and must also be of quality and have a nominal price match with financial capabilities. On the other hand, for fashion business players, currently, importing second-hand clothes is a big business area for new or second-hand clothes, business opportunities consider second-hand clothes business to have a small capital compared to new clothes. The purpose of this study was to determine the effect of partially and simultaneously on product quality and price variables on customer satisfaction who bought second-hand clothes at the Brandsek store in the Natural Gas Village, Muara Badak District. The analysis in this study is multiple regression, processed using SPSS, with a total of 37 respondents. The results of this study showed that the variables of product quality and price simultaneously had a significant effect on consumer satisfaction. Partially, product quality has a significant effect on consumer satisfaction and the price variable partially also has a significant influence on consumer satisfaction at the brandsek shop in the natural gas village of Muara Badak.